The Breeding of Waxy Sorghum Using Traditional Three-Line Method and Marker-Assisted Selection - Yong-Pei Wu; Yu-Chi Chang; Su-Chen Kuo; Dah-Jing Liao; Ting-Yu Shen; Hsin-I Kuo; Sheng-Wen Wang; Yu-Chien Tseng (Agriculture, 2023)
Sorghum (Sorghum bicolor) exhibits drought resistance and environmental adaptability, making it a crucial cereal crop for semi-arid regions. It has a wide range of uses, including as food, feed, brooms, alcohol production, and bioethanol. In particular, Taiwan imports nearly 50,000 tons of sorghum annually, primarily for the production of sorghum liquor. However, the ideal raw material for high-quality sorghum liquor is waxy sorghum, and not all sorghum varieties imported or promoted in Taiwan are of this waxy type. Consequently, there is a shortage of sufficient waxy sorghum raw materials to meet the demands of the Taiwan market. The occurrence of waxy sorghum (wx) is caused by the mutation of granule-bound starch synthase I (GBBS I), and there are currently several known types of mutants, carrying different wxa, wxb, and wxc waxy alleles. Among them, wxc is a novel mutation type, and in native sorghum in Taiwan, individuals with the waxy allele wxc have been found. The three-line method is a commonly used breeding strategy, which simplifies the process of emasculation to obtain hybrid F1 offspring. In this study, imported sorghum variety Liangnuo No.1 (with male sterility), native glutinous sorghum variety SB6 from Taiwan (carrying the wxc waxy allele), and sorghum reference genome variety BTx623 were used as research materials. The goal was to use the three-line method to produce waxy sorghums, including the male sterile line (A-line), male sterile maintenance line (B-line), and fertility-restoring line (R-line). The breeding results showed that by using backcross breeding, molecular-assisted selection, and traditional field selection methods, high-quality three-line materials (A-, B-, R-lines, named CNA1, CNB1 CNR1, respectively) and F1 hybrid (CNH1) with favorable agronomic traits and yield quality were successfully obtained.